Global perspectives, confidence and attitudes of health students post implementation of an online interprofessional wound care learning intervention: an international exploratory analysis from five countries. - Theobald, Karen Ann; O'Donnell, Deirdre; Johnston, Sandra; Neil, Sharon; Shepherd, Andrea; Lokeesan, Vignesvararjah; Nguyen, Thi Phuong Lan; Ababneh, Anas; Linh Tran, Thuy Khanh; Parker, Christina (Journal of Interprofessional Care)
This study explores the impact of an international, interprofessional online masterclass on wound care for health students from five countries. The aim was to evaluate students' knowledge, confidence, and attitudes toward interprofessional education (IPE) and collaborative care in wound management. A descriptive quantitative design was employed, utilizing pre- and post-masterclass surveys to assess participants' confidence in various aspects of wound care and their perceptions of teamwork in healthcare. Participants from nursing, medicine, and allied-health disciplines were included. The masterclass incorporated a case study, risk factors, and management strategies for wounds, delivered through an online platform with collaborative activities. Findings indicated improvements in students' confidence in wound assessment, management, and prevention in all wound types, dressings, and wound beds. Additionally, attitudes toward IPE showed positive shifts, with students valuing collaborative teamwork, role understanding, and person-centered care. Despite challenges, such as time-zone differences and limited exposure time, the study highlights the potential of IPE to enhance students' clinical practice and prepare them for multidisciplinary collaboration in wound care. These results suggest the possibility of incorporating IPE into healthcare curricula and emphasize the need for further research exploring long-term effect in wound care outcomes.